Local and landscape effects on the reproduction of wild bees and wasps in Mediterranean communities along a gradient of land-use - Marrero, Hugo Javier; Gómez-Martínez, Carmelo; Allasino, Mariana Laura; Haedo, Joana P.; González-Estévez, Miguel A.; Lázaro, Amparo (Wiley, 2025)
The transformation of natural landscapes for agricultural purposes may severely affect wild bee and wasp reproduction. In this study, we located trap-nests on 18 natural Mediterranean communities within agricultural areas to study the effects of landscape (% natural areas and heterogeneity) and local flowering communities (flower abundance and richness) on the total abundance and richness of solitary bees and wasps that nest within cavities. We also estimated several reproductive variables (number of nests, number of cells per nest, sex ratio, parasitoidism and survival) of the two most common species in the study system: the bee Osmia caerulescens and the wasp Ancistrocerus longispinosus. We found that total bee abundance increased with flower richness and landscape heterogeneity, while it decreased with flower abundance. Furthermore, our results indicated local and landscape effects on the focal species reproductive success, being stronger those at the local than at the landscape scale overall. Floral richness and abundance influenced the number of cells per nest. However, while the effect of flower abundance was positive in both cases, the effect of flower richness differed, being positive for O. caerulescens and negative for A. longispinosus. The percentage of natural habitats in the landscape had a positive additional effect on the number of cells per nest only in A. longispinosus. Besides, flower richness was positively related to the proportion of females in both species and increased O. caerulescens survival. Our findings stress the importance of considering different spatial scales for an effective conservation management that takes into account Hymenoptera reproduction.